Finding ways to carry on: stories of vulnerability in chronic illness - Synnes, Oddgeir (Int J Qual Stud Health Well-being, 2020)
Purpose: In this study, we explore the lived experiences of chronic illness in four groups of patients; children with asthma, adolescents with diabetes, young adults with depression, and adult patients with chronic, obstructive pulmonary disease (COPD). Persons living with chronic illness are often designated as vulnerable. This study builds on the assumption that being vulnerable belongs to being human, and that vulnerability also might entail strength and possibilities for growth. Methods: A narrative analysis was undertaken to illuminate how experiences of vulnerability were narrated across the four patient groups, presenting four individual stories, one from each of the patient groups. Results/conclusion: The stories illuminate how living with a chronic illness implies differing capabilities and capacities dependent on the specific condition. At the same time the stories point to how various abilities and challenges in living with chronic illness can be alleviated or seen as resources. Considered together, the stories underscore how ´finding ways to carry on´ in chronic illness requires interpretational work. By calling upon resources among significant others, in the surroundings and in oneself, the narrator can find ways of interpreting living with chronic illness that might open towards a hopeful future.